(untitled) (Bombay Hospital Journal, 2026)
INTRODUCTION Schwannomas are benign slow growing tumors that originate from the myelin sheath of the nerves; predominantly arising from the vestibular nerve in 90% of the cases. [1] Most schwannomas are sporadic and few are associated with NF1, Schwannomatosis, Carney’s complex etc. Among the non-vestibular schwannomas, only about 5% arise from the hypoglossal nerve; tumor composed purely of motor nerves. Most hypoglossal schwannomas are intracranial in location, followed by intracranial lesion with a secondary extracranial extension - most frequently in the parapharyngeal space. [2] Primary extracranial hypoglossal schwannoma is very rare. Among them, to this date, there are only 3 reported cases of hypoglossal nerve schwannoma located at the carotid bifurcation. [3,4,5] These tumors are often diagnosed late due to non-specific clinical history and examination findings. They are asymptomatic for many years and hence histopathology is the gold standard of diagnosis. [6] We hereby present a case of a 52 year old female who came with a slow growing painless mass in the right side of the neck.